Who replies to consultations, and what do they say? The case of broadband universal service in the UK. (September 2019) - Stocker, Volker; Whalley, Jason
Abstract: Over the last decade or so, access to broadband services has become increasingly important. While many in the UK already benefit from the provision of broadband, some, especially those located in more rural and remote areas, do not – they may not be able to access the Internet and when they do, their connection and consumer experience may be poor. After trying to resolve this through a stream of different initiatives, the UK government announced a broadband universal service obligation (USO) of 10 Mbps in late 2015. Ofcom, the telecommunications regulator, launched a consultation in April 2016 and sought the views of interested parties. The consultation attracted considerable interest, but after the submissions from orchestrated campaigns are discounted just over 100 responses remain. But who contributed and what did they say? To explore these two questions, this paper adopts a qualitative approach, using NVIVO, to analyse the responses to the consultation. We show that contributions were highly diverse, reflecting both the complexity of the issue as well as its politicised nature. A lack of agreement among the responses is revealed and divergent views on key issues like the appropriateness of 10 Mbps, whether this should change, how it should be funded or what technologies should be used exist. In this paper, we provide a critical discussion of and derive implications for the broadband USO. We tentatively conclude that those in rural and remote areas that the USO intends to help are caught between two countervailing forces – speed and cost deployment – that interact to ensure that whatever resolution to provide broadband access, some will likely be unhappy. Highlights: Contributions to the UK's universal service broadband consultation are diverse. Interaction between speed and cost shapes rural broadband availability. Lack of agreement regarding whether the proposed 10 Mbps USO is satisfactory. Illustrates the interplay between technology, economics and politics.